Effects of Porcine Immature Oocyte Vitrification on Actin Microfilament Distribution and Chromatin Integrity During Early Embryo Development in vitro - López, Alma; Ducolomb, Yvonne; Casas, Eduardo; Retana-Márquez, Socorro; Betancourt, Miguel; Casillas, Fahiel (Frontiers in Cell and Developmental Biology, 2021)
Vitrification is mainly used to cryopreserve female gametes. This technique allows maintaining cell viability, functionality, and developmental potential at low temperatures into liquid nitrogen at -196°C. For this, the addition of cryoprotectant agents, which are substances that provide cells protection during cooling and warming is required. However, they have been reported to be toxic, reducing oocyte viability, maturation, fertilization, and embryo development, possibly by altering cell cytoskeleton structure and chromatin. Previous studies have evaluated the effects of vitrification in the germinal vesicle, metaphase II oocytes, zygotes, and blastocysts, but the knowledge of its impact in their further embryo development is limited. Other studies have evaluated the role of actin microfilaments and chromatin, based on the fertilization and embryo development rates obtained, but not the direct evaluation of these structures in embryos produced from vitrified immature oocytes. Therefore, this study was designed to evaluate how the vitrification of porcine immature oocytes affects early embryo development by the evaluation of actin microfilaments distribution and chromatin integrity. Results demonstrate that the damage generated by the vitrification of immature oocytes affects viability, maturation, and the distribution of actin microfilaments and chromatin integrity, observed in early embryos. Therefore, it is suggested that vitrification could affect oocyte repair mechanisms in those structures, being one of the mechanisms that explain the low embryo development rates after vitrification.